A cross-sectional study: serum CCL3/MIP-1α levels may reflect lumbar intervertebral disk degeneration in Han Chinese people - Zhang YL; Li B; Zhou ZH (Journal of Pain Research, 2018)
Yi-Li Zhang,1,2,* Bei Li,1,2,* Zeng-Huan Zhou1 1School of Public Health, Southern Medical University, Guangzhou, Guangdong Province, People’s Republic of China; 2School of Health Services Management, Southern Medical University, Guangzhou, Guangdong Province, People’s Republic of China *These authors contributed equally to this work Background: The macrophage inflammatory protein-1α (MIP-1α), also named chemokine cytokine ligand 3 (CCL3), has been detected in nucleus pulposus and increased following cytokine stimulation. Objective: The current study was performed to explore the relationship between serum CCL3/MIP-1α levels with lumbar intervertebral disk degeneration (IDD). Patients and methods: A total of 132 disk degeneration patients confirmed by magnetic resonance imaging and 126 healthy controls were enrolled in the current study. Radiological evaluation of the IDD was conducted using a 3.0-T magnetic resonance imaging scanner for entire lumbar vertebra region. Degeneration of intervertebral disk was assessed by Schneiderman criteria. Serum CCL3/MIP-1α levels were investigated using a sandwich enzyme-linked immunosorbent assay. The Visual Analog Scale scores and Oswestry Disability Index index were recorded for clinical severity. Results: Elevated concentrations of CCL3 in serum were found in IDD patients compared with asymptomatic volunteers. The case group included 49 IDD patients with grade 1, 42 with grade 2, and 41 with grade 3. Grade 3 and 2 had significantly higher CCL3 concentrations in serum compared with those with grade 1. The serum CCL3 levels were positively related to the degree of disk degeneration. In addition, the serum CCL3 levels also demonstrated a significant correlation with the clinical severity determined by Visual Analog Scale scores and Oswestry Disability Index index. Conclusion: Serum CCL3 may serve as a biomarker of IDD. Keywords: chemokine cytokine ligand 3, intervertebral disk degeneration, cross-sectional study